2004
DOI: 10.1080/1071576042000206478
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of the Xanthate, D609, on Alzheimer's Amyloid β-peptide (1–42)-induced Oxidative Stress in Primary Neuronal Cells

Abstract: Tricyclodecan-9-yl-xanthogenate (D609) is an inhibitor of phosphatidylcholine-specific phospholipase C, and this agent also has been reported to protect rodents against oxidative damage induced by ionizing radiation. Previously, we showed that D609 mimics glutathione (GSH) functions and that a disulfide is formed upon oxidation of D609 and the resulting dixanthate is a substrate for GSH reductase, regenerating D609. Considerable attention has been focused on increasing the intracellular GSH levels in many dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 60 publications
1
62
0
Order By: Relevance
“…Recently, we showed that the xanthate D609, a glutathione mimetic [44], protects primary neuronal culture against Aβ (1-42)-induced oxidative stress and neurotoxicity in vitro [45] and against Aβ (1-42) in vivo [46]. D609 has the ability to scavenge hydrogen peroxide and hydroxyl free radicals [44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we showed that the xanthate D609, a glutathione mimetic [44], protects primary neuronal culture against Aβ (1-42)-induced oxidative stress and neurotoxicity in vitro [45] and against Aβ (1-42) in vivo [46]. D609 has the ability to scavenge hydrogen peroxide and hydroxyl free radicals [44].…”
Section: Discussionmentioning
confidence: 99%
“…Such inhibition decreases production of the secondary messenger diacylglycerol (DAG) that activates protein kinase C (PKC) and acidic sphingomyelinase (aSMase) [40]. However, with a free thiol group, D609 may also possess strong antioxidant activity [41] with in vitro and in vivo radical scavenging properties and inhibition of free radialinduced oxidative stress [42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We report here that ddC, at concentrations achievable in the CSF, induces oxidative stress when added to synaptosomes and isolated mitochondria. The levels of oxidative stress as measured by protein carbonyls on synaptosomes were significantly reduced upon the use of a known brain accessible antioxidant and glutathione mimetic [D609] (Zhou et al 2001;Lauderback et al 2003;Sultana et al 2004). In addition, we observed a significant reduction in the levels of the anti-apoptotic protein Bcl-2, a significant release of cytochrome c and an equally significant increase in caspase-3 protein levels upon treatment of mitochondria with ddC, suggesting the induction of apoptotic process following treatment with ddC.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, recent studies clearly suggest that neurotoxicity exerted by senile plaques arises from the induction of oxidative stress [49][50][51]. Furthermore, Pratico et al [52] reported that Al increased in vivo lipid peroxidation, as well as Al-accelerated Ab peptide formation and plaque deposition in amyloid precursor protein transgenic mice.…”
mentioning
confidence: 99%